2014
DOI: 10.1007/s11023-014-9351-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Representation of a Complex Motor Action Executed by Different Motor Systems

Abstract: The present study evaluates the cognitive representation of a kicking movement performed by a human and a humanoid robot, and how they are represented in experts and novices of soccer and robotics, respectively. To learn about the expertise-dependent development of memory structures, we compared the representation structures of soccer experts and robot experts concerning a human and humanoid robot kicking movement. We found different cognitive representation structures for both expertise groups under two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The measure of the invariance value λ ranges between 0 and 1, whereas 1 indicates the highest accordance between two structures. The statistical threshold for accepting invariance between two structures is set to λ = 0.68 as an empirically estimated value [ 33 , 34 , 36 , 37 , 39 ]…”
Section: Methodsmentioning
confidence: 99%
“…The measure of the invariance value λ ranges between 0 and 1, whereas 1 indicates the highest accordance between two structures. The statistical threshold for accepting invariance between two structures is set to λ = 0.68 as an empirically estimated value [ 33 , 34 , 36 , 37 , 39 ]…”
Section: Methodsmentioning
confidence: 99%
“…Most of the studies in sport are done to investigate the nature and role of mental representation in skilled athletic performance, and to derive new technologies in mental training and technical preparation (Schack and Hackfort 2007;Schack and Bar-Eli 2007;Schack 2004a). Findings from studies across sports, such as golf (Frank et al 2013), soccer (Lex et al 2015), tennis (Schack and Mechsner 2006), wind surfing (Schack and Hackfort 2007), volleyball (Schack 2004b), climbing (Bläsing et al 2014) and judo (Weigelt et al 2011) show that the mental representation structures relate to performance. These Fig.…”
Section: Studies About Mental Representation In Skilled Actionmentioning
confidence: 99%
“…According to this view, motor learning results from a change, modification, and development of representation structure in long‐term memory, which contain information about the perceptual effects of actions (Meier et al., 2020; Schack et al., 2021). The structural dimensional analysis of mental representation (SDA‐M) was employed to assess mental representation structures of different motor actions (Fazeli et al., 2017; Lex et al., 2015; Schack et al., 2007). Generally, it was found that skilled performers have a more structured mental representation than novices.…”
Section: Introductionmentioning
confidence: 99%